Continuous supercritical decrosslinking extrusion process for recycling of crosslinked polyethylene waste. Issue 6 (10th September 2014) - Baek, Bum Ki; Shin, Ji Wook; Jung, Jun Yong; Hong, Soon Man; Nam, Gi Joon; Han, Haksoo; Koo, Chong Min
ABSTRACT This work demonstrates that extrusion process can be used as a continuous reactor for the recycling of crosslinked polyethylene (XLPE) via supercritical methanol decrosslinking reaction. The multistage single screw extruder (L/D = 36, D = 40 mm) with methanol injection pump was customized for the continuous supercritical decrosslinking reaction. Reaction temperature was ranged from 360°C to 390°C. The amount of methanol was varied from 0 to 7 mL/min. The extruder provided the crosslinked polymers with the supercritical conditions of methanol during continuous process. The gel content of XLPE decreased with the increase in the reaction temperature and methanol content. Although XLPE experienced supercritical methanol for less than 2 min retention time in the continuous supercritical extruder, it was completely decrosslinked above 390°C at the methanol feeding rate of 7 mL/min. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41442.